PERBANDINGAN SISTEM HUKUM ANTARA INDONESIA DAN CHINA TERKAIT PERLINDUNGAN MEREK TERKENAL TIDAK TERDAFTAR - Djuliana Djuliana; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Indonesia and China have the same legal system, namely civil law and other legal systems related to ideology, customs, and beliefs (religion). This legal system influences the rules of commerce. The advantages of free trade are increased investment, cooperation with other countries, and benefits due to expanding product distribution. But behind these advantages, some parties have bad faith to commit fraud by using the name of a well-known brand. A well-known brand is a type of brand that has the highest level of fame, trust, quality, and familiarity with consumers. Several well-known brands have not been registered yet, but other parties are carrying out these marks. The protection of this unregistered mark only extends to well-known brands due to their reputation and proof that the mark is required. Both Indonesia's and China's Trademark Laws have protected these well-known unregistered marks because they originate from international law, namely TRIPs, the Paris Convention, and other legal sources. The purpose of making this scientific work is to find out how far the protection of this well-known mark has not been registered. The method of writing this scientific work uses a normative juridical method with a statutory approach. One alternative for countries that adhere to the principle of first-to-file protection is that foreign brands can register them through the Madrid Protocol. With this registration system, it makes it easier for foreign applicants to register their trademarks in other countries.Keywords: Comparison of legal systems, Well Known Trademarks, FreeTrade